NANS-CDG: Delineation of the Genetic, Biochemical, and Clinical Spectrum - den Hollander, Bibiche; Rasing, Anne; Post, Merel A.; Klein, Willemijn M.; Oud, Machteld M.; Brands, Marion M.; de Boer, Lonneke; Engelke, Udo F. H.; van Essen, Peter; Fuchs, Sabine A.; Haaxma, Charlotte A.; Jensson, Brynjar O.; et al. (Frontiers in Neurology, 2021)
Background: NANS-CDG is a recently described congenital disorder of glycosylation caused by bi-allelic genetic variants in NANS, encoding an essential enzyme in de novo sialic acid synthesis. Sialic acid at the end of glycoconjugates plays a key role in biological processes such as brain and skeletal development. Here, we present an observational cohort study to delineate the genetic, biochemical and clinical phenotype and assess possible correlations. Methods: Medical and laboratory records were reviewed with retrospective extraction and analysis of genetic, biochemical and clinical data (2016-2020). Results: Nine NANS-CDG patients (9 families, six countries) referred to the Radboudumc CDG Center of Expertise were included. Phenotyping confirmed the hallmark features including intellectual developmental disorder (IDD) (n=9/9; 100%), facial dysmorphisms (n=9/9; 100%), neurologic impairment (n=9/9; 100%), short stature (n=8/9; 89%), skeletal dysplasia (n=8/9; 89%), and rhizomelia (n=8/9, 89%). Newly identified features include ophthalmological abnormalities (n=6/9, 67%), an abnormal septum pellucidum (n=6/9; 67%), (progressive) cerebral atrophy and ventricular dilatation (n=5/9; 56%), gastrointestinal dysfunction (n=5/9; 56%), thrombocytopenia (n=5/9; 56%), and hypo-LDL-cholesterol (n=4/9; 44%). Biochemically, elevated urinary excretion of N-acetylmannosamine (ManNAc) is pathognomonic, the concentrations of which show a correlation with clinical severity. Genotypically, eight novel NANS variants were identified. Three severely affected patients harbored identical compound heterozygous pathogenic variants; one of whom was initiated on experimental prenatal (at 31 weeks gestational age) and postnatal treatment with oral sialic acid. This patient showed markedly better psychomotor development than the other two genotypically identical males. Conclusions: ManNAc screening should be considered in all patients with IDD, short stature with rhizomelia, facial dysmorphisms, neurologic impairment, an abnormal septum pellucidum +/- congenital and neurodegenerative lesions on brain imaging, to establish a precise diagnosis, and contribute to prognostication. Personalized management includes accurate genetic counselling and access to proper supports, and tailored care for gastrointestinal symptoms, thrombocytopenia and epilepsy as well as rehabilitation services for cognitive and physical impairments. Motivated by the short term positive effects of experimental treatment with oral sialic, we have initiated this intervention with protocolized follow-up of neurologic, systemic and growth outcomes in 4 patients. Research is ongoing to unravel pathophysiology and identify novel therapeutic targets.